2021
DOI: 10.3389/fimmu.2021.742914
|View full text |Cite
|
Sign up to set email alerts
|

Immune Profile and Clinical Outcome of Breakthrough Cases After Vaccination With an Inactivated SARS-CoV-2 Vaccine

Abstract: Constant efforts to prevent infections by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are actively carried out around the world. Several vaccines are currently approved for emergency use in the population, while ongoing studies continue to provide information on their safety and effectiveness. CoronaVac is an inactivated SARS-CoV-2 vaccine with a good safety and immunogenicity profile as seen in phase 1, 2, and 3 clinical trials around the world, with an effectiveness of 65.9% for symptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 40 publications
5
35
0
1
Order By: Relevance
“…Although the study design did not allow the calculation of true efficacy for the vaccine due to the absence of a placebo arm, we demonstrate that in a scenario of high viral circulation [ 3 ], the vast majority of COVID-19 cases developed by vaccinated participants were only mild. Only two participants aged over 60 years required hospitalizations, and no deaths due to COVID-19 occurred as part of the study [ 28 ]. Accordingly, we have previously published seroconversion data for COVID-19-infected participants showing high titers of anti-RBD antibodies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the study design did not allow the calculation of true efficacy for the vaccine due to the absence of a placebo arm, we demonstrate that in a scenario of high viral circulation [ 3 ], the vast majority of COVID-19 cases developed by vaccinated participants were only mild. Only two participants aged over 60 years required hospitalizations, and no deaths due to COVID-19 occurred as part of the study [ 28 ]. Accordingly, we have previously published seroconversion data for COVID-19-infected participants showing high titers of anti-RBD antibodies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 However, severity of disease due to SARS-CoV-2 breakthrough infections and confounding risk factors for breakthrough infections were not compared between patients and controls. Other studies in healthy individuals observed associations between reduced humoral responses after SARS-CoV-2 vaccination and an increased incidence of SARS-CoV-2 breakthrough infections and possibly more severe disease, 7 , 8 , 9 but there is a paucity of data from patients with immune-mediated inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ongoing phase 3 clinical trial in Chile has described an increase in the levels of IgG and neutralizing antibodies in adults aged 18-59 years and ≥ 60 years two- and four-weeks after the second dose of CoronaVac ® 56 . In addition, this vaccination promotes the activation of a T cell immune response against SARS-CoV-2 antigens in a 0-14 immunization schedule 5 (two-weeks interval), being an effective vaccine to prevent COVID-19 7, 8 . In Chile, 93.7% of the target population has received a first vaccine dose, and 91.4% were fully vaccinated with CoronaVac® on December 10 th of 2021 in a 0-28 days vaccination schedule 9 .…”
Section: Introductionmentioning
confidence: 99%